2023
DOI: 10.3389/fnut.2023.1276940
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and lifestyle oxidative balance scores are independently and jointly associated with nonalcoholic fatty liver disease: a 20 years nationally representative cross-sectional study

Yuanbin Liu,
Mingkai Chen

Abstract: BackgroundOxidative stress is an important contributor to the progression of nonalcoholic fatty liver disease (NAFLD), but whether dietary and lifestyle pro- and antioxidants may have combined or independent effects on NAFLD, and advanced liver fibrosis (AHF) remains unclear. We aimed to elucidate the relationship between a well-established oxidative balance score (OBS) and NAFLD/AHF.MethodsThis was a cross-sectional study. We included adult participants with complete data from the National Health and Nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Consequently, there is a need for a comprehensive assessment of index-OBS to evaluate oxidative balance in individuals and to investigate the impact of this balance on MASLD. Prior investigations have examined the potential benefit of this index on NAFLD through inflammation, oxidative stress, and glycolipid metabolism (38). By the way, OBS is not associated with progression of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a need for a comprehensive assessment of index-OBS to evaluate oxidative balance in individuals and to investigate the impact of this balance on MASLD. Prior investigations have examined the potential benefit of this index on NAFLD through inflammation, oxidative stress, and glycolipid metabolism (38). By the way, OBS is not associated with progression of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have previously demonstrated the viability of OBS using the NHANES database. We defined the OBS utilizing well-validated components and calculation schemes derived from prior NHANES investigations ( 11 , 16 ). The OBS comprises the dietary OBS, consisting of 16 dietary components, and the lifestyle OBS, comprising 4 lifestyle components.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, antioxidant-based dietary and lifestyle interventions have attracted attention as potential strategies to diminish the risk of NAFLD progression and related complications. Despite an incomplete understanding of NAFLD's pathogenesis, numerous studies have emphasized the pivotal role of oxidative stress, stemming from an imbalance in oxidative and antioxidant processes, in the initiation and progression of NAFLD (9)(10)(11). Dietary and lifestyle adjustments rich in antioxidants, such as regular exercise and smoking cessation, have been proposed (12).…”
Section: Introductionmentioning
confidence: 99%
“…We constructed and calculated OBS on the basis of previous studies. In this study, the OBS was composed of four lifestyle factors and 16 dietary components ( 13 , 21 ). The dietary factors were classified into prooxidants (total fat and iron) and antioxidants (β-carotene, dietary fiber, copper, vitamin B6, vitamin B12, vitamin C, niacin, vitamin E, total folate, vitamin B2, magnesium, calcium, zinc, and selenium) according to the effect on oxidative stress.…”
Section: Methodsmentioning
confidence: 99%